Circadian clock period length is not consistently linked to chronotype in a wild songbird - Tomotani, Barbara; Strauß, Aurelia; Kishkinev, Dmitry; van de Haar, Huib; Helm, Barbara (European Journal of Neuroscience, 2024)
Circadian clock properties vary between individuals and relate to variation in entrained timing in captivity. How this variation translates into behavioural differences in natural settings, however, is poorly understood. Here we tested in great tits whether variation in the free-running period length (tau) under constant dim light (LL) was linked to the phase angle of the entrained rhythm (“chronotype”) in captivity and in the wild, as recently indicated in our study species. We also assessed links between tau and the timing of first activity onset and offset under LL relative to the last experienced light-dark (LD) cycle. We kept 66 great tits, caught in two winters, in LL for 14 days and subsequently released them with a radio transmitter back to the wild, where their activity and body temperature rhythms were tracked for 1 to 22 days. For a subset of birds, chronotype was also recorded in the lab before release. Neither wild nor lab chronotypes were related to tau. We also found no correlation between lab and wild chronotypes. However, the first onset in LL had a positive relationship with tau, but only in males. Our results demonstrate that links between tau and phase of entrainment, postulated on theoretical grounds, may not consistently hold under natural conditions, possibly due to strong masking. This calls for more holistic research on how the many components of the circadian system interact with the environment to shape timing in the wild.
Keywords: Neuroscience; Zoology; Animal Physiology; Not aligned; Parus major; tau; activity rhythm; telemetry; diel rhythm; great tit